Konstruksi Pekerja Ideal dalam Dokumen Rekrutmen Korporat Indonesia: Studi Kasus atas Kriteria Kompetensi dan Karakter melalui Lensa Modal Bourdieu - Achmad Jauharil Muzakki (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines how professional suitability is constructed in corporate recruitment documents in Indonesia, addressing the tendency of employability research to treat employability primarily as a measurable individual attribute. Using a qualitative document analysis approach, the study analyzes two documents: the 2025 Sustainability Report of PT Astra International Tbk and the official careers portal of PT Bank Central Asia Tbk. These documents are interpreted through Bourdieu's theory of capital and conceptually compared with Rivera's (2012) findings on cultural matching in recruitment within elite professional service firms in the United States. The findings show that both documents construct professional suitability through the explicit integration of technical competencies and personal characteristics, the framing of cultural capital (particularly foreign language proficiency) as an explicit added value, and the institutionalization of interpersonal assessment mechanisms (